The first clinical experience on efficacy of topical flutamide on melasma compared with topical hydroquinone: a randomized clinical trial - Adalatkhah H; Sadeghi-Bazargani H (Dove Medical Press, 2015)
Hassan Adalatkhah,1 Homayoun Sadeghi-Bazargani2,3 1Department of Dermatology, Ardabil University of Medical Sciences, Ardabil, Iran; 2Road Traffic Injury Research Center, Department of Statistics and Epidemiology, Tabriz University of Medical Sciences, Tabriz, Iran; 3Department of Public Health Sciences, Karolinska Institute, Stockholm, Sweden Background: Treatment of melasma is unsatisfactory most of the times. Hormonal role is shown to exist in pathogenesis of the melasma, and sex-hormone related drugs may have an effect on melasma.Aim: To investigate efficacy of 1% flutamide cream versus 4% hydroquinone cream on melasma.Methods: In a parallel randomized clinical trial, 74 women with melasma were allocated to receive a sunscreen along with 4% hydroquinone cream or 1% flutamide cream. Melasma Area and Severity Index (MASI), mexameter melanin assay, and patient satisfaction were investigated.Results: Mean age of the participants was 33.8 years. Mean length of time suffering from Melasma was 96.3 months. The subjects reported in average 1.1 hours per day of exposure to sunlight. Mean standardized total patient satisfaction score was 28.8 (standard deviation [SD] 17.2) in flutamide group patients versus 18 (SD 15.5) in control group (P<0.01). Regardless of treatment group, the skin darkness assessed upon MASI scales was reduced over the treatment course (P<0.001). Using mixed effects, longitudinal modeling showed better treatment efficacy based on MASI scale for flutamide group compared to the hydroquinone group (P<0.05). However, longitudinal analysis of mexameter scores did not reveal any significant difference in melanin measurements between flutamide and hydroquinone.Conclusion: Topical flutamide appeared as effective as topical hydroquinone in treating melasma using mexameter assessment but with a better MASI improvement trend and higher patient satisfaction in flutamide treatment versus topical hydroquinone. As the present study is possibly the first clinical experience on efficacy of topical flutamide on melasma, it would be quite unreasonable to recommend clinical use of it before future studies replicate the results on its efficacy and safety. Keywords: Pigmentation disorders, topical, treatment, dermatology, anti-androgenic agents, acquired increased skin pigmentation, Melasma Area and Severity Index (MASI) Mexamete